Heart failure presented with massive pleural effusion and mediastinal lymphadenopathy: a rare case report (Bangladesh Journal of Medicine, 2014)
Heart failure may present with diverse manifestation. It is far most common cause of bilateral transudative pleural effusion. In very unusual case, it may present with only massive transudative pleural effusion without cardiomegaly and other features of heart failure such as leg odema, tender hepatomegaly or congested liver. We presented a case that present with massive transudative pleural effusion with mediastinal lymphadenopathy evidenced by CT scan of chest and treated successfully with diuretics. DOI: http://dx.doi.org/10.3329/bjmed.v24i2.20223 Bangladesh J Medicine 2013; 24 : 86-88